Analysis of Suspected Factors in Tuberculosis Cases in Semarang City Using a Logistic Regression Model - Ihsan Fathoni Amri; Febrian Hikmah Nur Rohim; Muhammad Ivan Ardiansyah; Farid Sam Saputra; Supriyanto; Ariska Fitriyana Ningrum; Arman Mohammad Nakib (PT. Teknologi Futuristik Indonesia, 2025)
Tuberculosis (TB) is one of the world's deadliest infectious diseases, with Indonesia being among the countries with the highest TB burden. Semarang City, as an urban area with a dense population, faces significant challenges in controlling TB, particularly among vulnerable populations. This study identifies significant risk factors influencing TB incidence in Semarang City using a binary logistic regression model. Descriptive analysis reveals an imbalance in the data, with the majority of patients categorized as